Great tits provided with ad libitum food lay larger eggs when exposed to colder temperatures. (27th February 2013) - Schaper, Sonja V.; Visser, Marcel E.
<x xml:space="preserve">Abstract</x> The amount of nutrients deposited into a bird egg varies both between and within clutches of the same female. Larger eggs enhance offspring traits, but as a tradeoff, laying large eggs also infers energetic costs to the female. Income breeders usually lay larger eggs later in the season, when temperatures and food availability are higher. Egg size is thus affected by the daily amount of energy available to produce an egg under cold conditions, but it is less well known in how far temperature exerts direct effects on egg size. We show that great tit females Parus major with access to ad libitum food and breeding in climate‐controlled aviaries varied their egg investments. The size of an individual egg was best predicted by mean temperatures one week pre‐laying, with females laying larger, rather than smaller, eggs under colder conditions. Eggs increased in size over the season, but not significantly over the laying sequence. The degree of daily temperature fluctuation did not influence egg size. In addition to a substantial between‐female variation, sisters were more similar to each other than unrelated females, showing that egg size does also reflect heritable intrinsic female properties. Natural variation in egg size is thus not only determined by energy‐limitation, but also due to females allocating more resources to eggs laid in colder environments, thus increasing early survival of the chicks. That the positive correlation between temperature and egg investments that is found in a natural population is reversed under ad libitum food conditions demonstrates that wild great tits tradeoff own condition with survival prospects of their chicks as a function of available food, not ambient temperature.